Strategic Planning Pitfalls in Society 5.0: A Systematic Literature Review - Daniel Mandel Gandrita; David Pascoal Rosado (Mediterranean Journal of Social Sciences, 2022)
Although strategic planning relevance has its ups and downs, it has shown that it can always be a reference point to guide managers and management. This paper aims to clarify if the strategic planning pitfalls identified in the mid-90s still apply to today's reality. Also, to validate strategic planning's importance in society 5.0 while exploring its barriers from a dynamic capability’s perspective. A bibliometric analysis focused on strategic planning pitfalls and the use of indexed journals/citations to validate the study relevance. To achieve this purpose, this study performs a systematic literature review and content analysis of 68 articles from 37 journals. The main results of strategic planning research revealed: (1) The relevance of strategic planning in society 5.0, (2) the appliance of dynamic capabilities creating a defensive business model, and (3) the two essential dimensions which can impact most strategic planning, and (4) the new pitfalls in today’s context. Guided by dynamic capabilities theory, this paper seeks to promote insights related to the importance of strategic planning, adds value to the body of knowledge, and identifies contingency considerations that help explain the results on the relationship between strategic planning and the present context. Received: 1 July 2022 / Accepted: 29 August 2022 / Published: 2 September 2022